2021
DOI: 10.1101/2021.12.13.472494
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Geometry of Representational Drift in Natural and Artificial Neural Networks

Abstract: Neurons in sensory areas encode/represent stimuli. Surprisingly, recent studies have suggest that, even during persistent performance, these representations are not stable and change over the course of days and weeks. We examine stimulus representations from fluorescence recordings across hundreds of neurons in the visual cortex using in vivo two-photon calcium imaging and we corroborate previous studies finding that such representations change as experimental trials are repeated across days. This phenomenon h… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 39 publications
3
5
0
Order By: Relevance
“…Third, we found a strong drift of population activity on the timescale of minutes within the recording session, whose features differed along the hierarchy. In V1 and PM, we found that drift, defined by a significant encoding of elapsed time within the session, also preserved the representational geometry of the evoked responses, consistent with previous experimental and modeling studies [Deitch et al, 2021, Aitken et al, 2021, Qin et al, 2023. On the other hand, RSP showed significant encoding of elapsed time within a session, but the representational geometry of evoked responses to sensory stimuli did not generalize across epochs, suggesting that relevant dimensions for RSP activity may not be stimulus specific, but potentially more related to overall environmental context.…”
supporting
confidence: 90%
“…Third, we found a strong drift of population activity on the timescale of minutes within the recording session, whose features differed along the hierarchy. In V1 and PM, we found that drift, defined by a significant encoding of elapsed time within the session, also preserved the representational geometry of the evoked responses, consistent with previous experimental and modeling studies [Deitch et al, 2021, Aitken et al, 2021, Qin et al, 2023. On the other hand, RSP showed significant encoding of elapsed time within a session, but the representational geometry of evoked responses to sensory stimuli did not generalize across epochs, suggesting that relevant dimensions for RSP activity may not be stimulus specific, but potentially more related to overall environmental context.…”
supporting
confidence: 90%
“…Our findings thus raise additional questions about the complex neural dynamics in V1, offering a basis for comparison with other modeling studies. For example, our approach contrasts with a recently published study by Aitken et al (2023), which also employs the same experimental paradigm developed by Garrett et al (2020Garrett et al ( , 2023. Aitken et al focus on elucidating a biologically plausible mechanism of synaptic plasticity, capable of reproducing novelty effects across different timescales, while also simulating individual neurons to describe their responses and diversity; however, they do not extensively seek the specific circuitry changes or their parametric details.…”
Section: Extensive Sampling Of the Solutions Finds Coordinated Shift ...mentioning
confidence: 95%
“…However, we did not include those in our modeling framework because it will require a model to have multiple channels of image inputs and a mechanism that changes the response to the images within the same condition, thus complicating the model. Besides, responses to such contextual novelty have been already described using synaptic plasticity (Aitken et al, 2023;Schulz et al, 2021). Therefore, we selected data segments around omission as the target data for our model, as these observations underscore the complex interplay between the circuit elements in V1, particularly in the interaction between absolute and omission novelty.…”
Section: Stimulus Novelty Influences the Responses Of V1 Neurons To I...mentioning
confidence: 99%
“…A similar mechanism is potentially helpful in the brain, too. And drift leads to similar results as dropout (Aitken et al, 2021). Sup.…”
Section: Part V Discussionmentioning
confidence: 70%
“…This is mostly achieved by homeostatic plasticity. Random drift, however, might be useful, too, both from a psychological point of view to overcome trauma (Richards and Frankland, 2017) and from a theoretical point of view to prevent overfitting (Aitken et al, 2021). The need for stability and flexibility depends on the situation.…”
Section: Plasticity and Driftmentioning
confidence: 99%